2014
DOI: 10.4103/0974-2069.126538
|View full text |Cite
|
Sign up to set email alerts
|

Early and 1-year outcome and predictors of adverse outcome following monocusp pulmonary valve reconstruction for patients with tetralogy of Fallot: A prospective observational study

Abstract: Background and Objectives:Repair of tetralogy of Fallot (TOF) with monocusp pulmonary valve reconstruction prevents pulmonary regurgitation (PR) for a variable period. Since postoperative outcome is governed by PR and right ventricular function, we sought to assess the severity of pulmonary regurgitation and right ventricular outflow (RVOT) gradient in the immediate postoperative period and at 1 year and attempted to identify the anatomical substrates responsible for adverse outcomes.Methods:The study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
2
18
1
Order By: Relevance
“…Furthermore, the monocusp is simple, inexpensive, and reproducible [ 11 ]. However, Sasikumar et al [ 12 ] reported that calcification and loss of mobility were observed in a significant number of patients 1 year after the operation. Additionally, some studies have reported a significant incidence of inherent valvular insufficiency and/or obstruction [ 7 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the monocusp is simple, inexpensive, and reproducible [ 11 ]. However, Sasikumar et al [ 12 ] reported that calcification and loss of mobility were observed in a significant number of patients 1 year after the operation. Additionally, some studies have reported a significant incidence of inherent valvular insufficiency and/or obstruction [ 7 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, it has been reported that the monocusp technique, which has controversial mid and late-term results and seems to have limited durability, has at least adequate function at an early stage and the potential to reduce postoperative mortality and morbidity. [5,12,13] In conclusion, we believe that, considering the early and late benefits, when pulmonary annulus diameter is adequate, every effort should be made to protect the pulmonary valve in patients undergoing total repair for tetralogy of Fallot. In patients with narrow pulmonary annulus undergoing transannular patch, monocusp insertion is a technique that could potentially reduce postoperative morbidity and mortality by conserving function of the pulmonary valve and right ventricle in the early stage.…”
Section: Discussionmentioning
confidence: 95%
“…The monocusp may be constructed with various materials such as autogenous or bovine pericardium, polytetrafluoroethylene (PTFE) membrane, and extracellular matrix. [12,13] In standard practice, the monocusp is prepared by cutting it as a semicircle to fit the length of the RVOT incision from the apex to the pulmonary annulus and the width of the diameter of the pulmonary annulus. The monocusp is attached by leaving 1 mm excess on both sides and suturing it to the pulmonary valve commissures and the apex of the RVOT incision at three different points.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations